THE CONSTRUCTION OF NEWS TICKERS IN THE ARABIC CHANNELS: (Al Arabiya TV - study of the case - 2007) - Jasem, Raad (ALBAHITH ALALAMI, 2008)
While providing important news information, News tickers ( also called sliders or crawlers ) have become one of the methods used daily by satellite channels, because it’s almost a continuous news coverage and as it seems, it has become today an addition to the news world. Hence, satellite channels need to look for a mechanism to build news tickers in order to develop them even though they are still today not recognisable and in need of being classified in a radio or television art, and that is not easy. This research sheds light on the construction of the slider of a news satellite channel, which is important according to our modest convictions, as it can be the beginning of a long scientific research in a new field of study. The problem of our research resides in the feelings of the researchers as they find weakness and ambiguity in the construction of Al Arabiya TV’s slides, in order to show how this can take effect, we need to answer the following problematics: 1- How readable are Al Arabiya TV’s sliders ? 2- Are Al Arabiya TV’s sliders interesting ? and is this interest in accordance with the standards adopted for a good journalistic writing ? The research aims at: 1- identifying the reasons behind the weakness of Al Arabiya TV’s sliders. 2- Determining the ambiguity of Al arabiya TV’s sliders according to the adopted readability standards.